BIMBINGAN TEKNIK LAPORAN KEUANGAN BADAN USAHA MILIK DESA KARYA MANDIRI DESA CIBODAS LEMBANG - Hanifah; Rari Dwi, Dita (Universitas PGRI Yogyakarta, 2023)
The establishment of BUMDes is determined through a regional regulation approved by the BPD referring to the laws and regulations. This movement is in line with the national movement to create 5,000 independent villages through village funds to develop BUMDes capital. As a village financial institution that meets the needs of micro-scale businesses in the village, BUMDes is obliged to make transparent and accountable financial reports per month and provide reports on its business development to the village community at least twice a year through village meetings. PKM activities are carried out with the aim of assisting the manager of BUMDes Karya Mandiri in Cibodas Village in preparing financial reports. This is expected to affect the performance of the BUMDes financial report when there is an audit of the BUMDes financial report by the BUMDes Supervisor. The solution provided in PKM activities, namely by conducting BIMTEK activities for BUMDes managers related to the preparation of financial reports. The first stage provides knowledge regarding the need for financial statements and the concepts of financial statements based on SAK ETAP. The second stage is to carry out technical guidance activities related to the preparation of financial reports based on transactions that occur in BUMDes. The third stage is monitoring to monitor the achievement of the PKM program targets. The target to be achieved is to increase the skills and knowledge of the BUMDes Karya Mandiri management regarding the preparation of financial reports so that they can produce good and correct financial reports in accordance with SAK ETAP.